Práticas de medir e formação de professores: reflexões sobre o passado (Revista Cocar, 2019)
The practical activities of measuring and training teachers: reflections on the pastResumoO presente artigo convida o leitor a refletir sobre a história do medir na escola primária. Indaga-se se o conhecimento do passado sobre as propostas de práticas de medir, no século XIX, para os anos inicias de escolarização, pode trazer contribuição para os professores. Analisam-se seis manuais de geometria e de desenho do século XIX e evidenciam-se duas representações distintas: a prática intuitiva de medir e a prática tradicional de medir com instrumentos. Ao final, problematiza-se resultados de estudos atuais sobre medidas de comprimentos com as representações construídas historicamente questionando a inserção de atividades desenvolvidas no século XIX na formação de professores.Palavras-chave: século XIX. Método Intuitivo. História da educação matemática. Formação de professores que ensinam matemática. AbstractThis article invites the reader to reflect on the history of measuring in primary school. It is questioned whether the knowledge of the past about the proposals of practices to measure, in the nineteenth century, for the initial years of schooling, can bring contribution to the teachers. Six manuals of geometry and drawing of the nineteenth century had analyzed and two distinct representations had evidenced: the intuitive practice of measuring and the traditional practice of measuring with instruments. At the end, we are discussing the results of current studies on measures of lengths with historically constructed representations and questions the insertion of activities developed in the nineteenth century in teacher training.Keywords: 19th century. Intuitive Method. History of mathematical education. Training of teachers who teach mathematics.